Penerapan pembelajaran STAD berbantuan media PANAMA untuk meningkatkan keterampilan berhitung - Oktaviani, Nisrina; Rahmawati, Puji; Suryawan, Ari; Nugroho, Widi (Mahesa Research Center, 2024)
This research aims to determine the improvement of Mathematics calculation skills by implementing STAD learning assisted by PANAMA media (Mathematics Napier Board). This research is Classroom Action Research (PTK) with the research subjects being 27 class IV students at SD Negeri Depok 1, Sleman. The object of this research is mathematical calculation skills in the arithmetic operations of multiplication and division. The instrument used in this research was test questions supported by observation sheets. The results of the research at the pre-cycle stage showed a class average of 68.07 with the number of students completing only 10 students or 37.0%. These results increased significantly after taking action in cycle I with a class average of 81.18 and in cycle II the class average was 90.59. In cycles I and II, it was seen that there was an increase in Mathematics calculation skills by 22.2% with the number of students who achieved KKTP at the end of cycle II being 23 students or 85.1%. Based on these results, it can be concluded that the application of STAD learning assisted by PANAMA media) can improve calculation skills, especially in the calculation operations of multiplication and division.